The South Georgia Pintail Anas g. georgica in captivity: history, m anagem ent and implications for conservation - Martin, A R (Wildfowl, 2013)
The South Georgia Pintail is the southernm ost w aterfow l taxon and an island endemic which survives year-round in some of the most hostile conditions encountered by any waterfowl. The wild population is cu r.